Long-term treatment response after intravitreal bevacizumab injections for patients with central serous chorioretinopathy - Kang, Hae Min; Choi, Jeong Hoon; Koh, Hyoung Jun; Lee, Sung Chul (PLOS ONE, 2020)
Purpose To investigate long-term treatment response after intravitreal bevacizumab injections (IVBIs) for central serous chorioretinopathy (CSC). Methods This retrospective, interventional study investigated the medical records of 45 eyes of 44 patients with CSC who underwent IBVIs and completed at least 2-year follow-up period. Complete resolution (CR) was defined as complete resolution of subretinal fluid at least 3 months after the last IVBI. Thick-choroid CSC was defined as mean subfoveal choroidal thickness more than 300.0 μm. The main outcome measure was long-term treatment outcome after IVBIs in patients with CSC. Results Thirty-five patients (79.5%) were male, and their mean age was 45.5 ± 9.6 years. The mean follow-up period was 35.1 ± 11.5 months. Twenty-two eyes (48.9%) had acute CSC, and 40 eyes (88.9%) achieved CR. Twenty eyes (50.0%) developed recurrence, the mean number of IVBIs to achieve the first CR was not significantly different between eyes with and without recurrences (2.6 ± 1.6 vs. 2.9 ± 1.9; P = 0.658). Thick-choroid CSC was significantly difference between the eyes with and without recurrence (17 eyes, 85.0% vs. eyes, 50.0%; P = 0.020). Among the baseline characteristics, serous pigment epithelial detachment (B = - 2.580, P = 0.032) and thick-choroid (B = 1.980, P = 0.019) were significantly associated with recurrence. Conclusion Eyes with CSC treated with IVBI and achieving complete resolution of subretinal fluid have 50% chance of recurrence in the long term. Thinner choroid and serous pigment epithelial detachment appear protective for recurrences.